2023
DOI: 10.1186/s12912-023-01178-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of professional identity on how the receiver receives and responds to a speaking up message: a cross-sectional study

Abstract: Background Research focused on understanding what enables or hinders health professionals to speak up about a safety concern has been to date predominately atheoretical and speaker focused. However, the role the receiver of the message plays in these often-difficult encounters is highly influential. To date, speaking up programs have created conversational mnemonics that technically should respectfully engage the receiver, yet speaking up remains challenging. This paper utilises Communication A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…Whiting, Maynes [ 18 ] suggested future studies need to ascertain how group membership of the voicer (speaker) and rater (receiver), could possibly influence these outcomes. Our study confirms that speaking up conversations within the health context are strongly influenced by group membership, as defined by clinical discipline and seniority [ 25 ]. We recommend further research needs to be undertaken to see if the inclusion of recommendations as a generic and standard speaking up process enhances or inhibits message reception, and in what context (low or high stakes situations).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Whiting, Maynes [ 18 ] suggested future studies need to ascertain how group membership of the voicer (speaker) and rater (receiver), could possibly influence these outcomes. Our study confirms that speaking up conversations within the health context are strongly influenced by group membership, as defined by clinical discipline and seniority [ 25 ]. We recommend further research needs to be undertaken to see if the inclusion of recommendations as a generic and standard speaking up process enhances or inhibits message reception, and in what context (low or high stakes situations).…”
Section: Discussionsupporting
confidence: 84%
“…Schwappach and Gehring [ 32 ] found that the presence of the patient inhibited speaking up, mostly due to the speaker’s desire not to humiliate a colleague in public or lose patient trust. Our work across multiple receiver focused studies has found that indeed, the presence of an audience consistently influences the receiver’s reactions and responses, particularly nurses and midwives and when the speaker uses less accommodative language [ 25 , 46 ]. Clearly, to enhance message reception, both the speaker and receiver need to negotiate not just the raised concern, but also the context in which the conversation occurs (in nonlife-threatening situations).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations